Reference values for the cervical spinal canal and the vertebral bodies by MRI in a general population - Nell, Christopher; Bülow, Robin; Hosten, Norbert; Schmidt, Carsten Oliver; Hegenscheid, Katrin (PloS one, 2019)
To provide population-based reference values for cervical spinal canal parameters and vertebral body (VB) width and to study their associations with sex, age, body height, body weight and body mass index (BMI) using MRI. Cross-sectional analyses included data from 2,453 participants, aged 21-89 years, of the population-based Study of Health in Pomerania (SHIP) who underwent whole-body MRI at 1.5 Tesla between July 2008 and March 2011. A standardised reading was performed for the C2-C7 cervical spine levels at sagittal T2 TSE weighted sequences. Reference intervals for spinal canal parameters were similar in males and females, while VB width was on average 2.1-2.2 mm larger in males. Age effects were only substantial regarding VB width with a 0.5 mm per ten-year age increase. Body height effects were only substantial regarding the osseous spinal canal and VB width. Body weight and BMI effects are mostly not substantial. Our study provides MRI-based reference values for the cervical spinal canal parameters in an adult Caucasian population. Except for VB width, associations with sex, age and somatometric measures are mostly small and thus have only limited clinical implications. Some available cut-off values may need a revision because they likely overestimate risks.